THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP STYLE AND EMPLOYEE LOYALTY ON EMPLOYEE PERFORMANCE PT. SMART TALENTA MULTITAMA - Haryanti, Haryanti; Zulganef, Zulganef (International Journal of Global Operations Research, 2023)
The purpose of this study was to examine the effects of employee loyalty on employee performance as well as the influence of transformational leadership style and employee loyalty on employee performance. At PT Smart Talenta Multitama is a partner organization that provides training, organizational development, legal advice, and human resource management services, a total of 45 employees participated in this quantitative study, all the employees served as respondents, and used of multiple regression in data analysis. According to the regression coefficient value of 0.234 obtained from the results, states that transformational leadership style had a positive and significant impact on employee performance. Employee loyalty also demonstrated a positive and significant impact on employee performance with a regression coefficient value of 0.699, and these results indicate that both transformational leadership style and employee loyalty have an impact on employees' performance.